Low-Birth-Weight Babies During the Coronavirus Disease-2019 Pandemic: A Descriptive Study - Endang Wahyuningsih (Indonesian Journal of Global Health Research, 2022)
Coronavirus disease-2019 (COVID-19) has become a non-natural disaster that has an impact on everyone. Maternal mortality and neonatal mortality in Indonesia are still a big challenge and need attention in the COVID-19 disaster situation. Neonatal deaths reported that the most deaths occurred in the first six days of life. The highest cause of neonatal death in 2019 was Low-Birth-Weight (LBW). LBW is usually caused by the mother's condition during pregnancy (adolescent pregnancy, malnutrition, and pregnancy with complications), twins' pregnancy, congenital fetal anomalies, and placenta disorder that inhibit the baby's growth (Intra Uterine Growth Restriction (IUGR)). This study aimed to determine the incidence of LBW during the pandemic at the Public Health Center of Juwiring, Klaten. The method of this study was a descriptive study. The sample in this study was total sampling using secondary data from October 2020 - June 2021 as many as 35 babies, and data analysis using univariate analysis. The results showed that the babies in category of LBW were 30 (85.7%), Very-Low-Birth-Weight (VLBW) was 3 (8.6%), and Extremely-Low-Birth-Weight (ELBW) was 2 (5.7%). The findings of this study from the maternal age group under 35 years old are 32 (91.4%), the multipara parity was 21 (60%), and the gestational age under 37 weeks was 22 (62.9%).